Main line railways delegate information : Tuesday 1 October 1996 (Thomas Telford, 1996)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of infrarail seminar held in Manchester on 1 October 1996.